Factores predisponentes para la condición de respiradores bucales, revisión bibliográfica - Rojas Escobar, Thalía Cecibel (2021)
This research corresponds to a qualitative, descriptive and documentary bibliographic review, the study was carried out using exclusion and inclusion criteria, for this, several scientific articles based on Oral Respirators were analyzed, which aimed to recognize the different factors that lead to a patient to develop the bad habit of breathing through the mouth, in addition to analyzing each of the factors describing their clinical characteristics and being able to detail the different treatments to counteract the effects that the pathology may produce. 28 documentary-type articles were considered from 2014 to 2020, bibliographic reviews, clinical cases, books, as well as theses that helped organize the information. Within the study we can highlight that hypertrophy of adenoids and tonsils as well as allergic rhinitis together with deviation of the nasal septum and idiopathic hypertrophy of turbinates are the main factors that lead to mouth breathing, within the clinical characteristics we have crowding, protrusion, open bite, incompetent lip closure, long and narrow face, narrow and deep palate. Regarding treatments, we have as main myofunctional therapy, orthopedic treatments such as the multifunctional dental splint KEYWORDS: ORAL RESPIRATOR / ETIOLOGY / CLINICAL MANIFESTATIONS / TREATMENT.